StaTips Part II: Assessment of the repeatability of measurements for continuous data - Perinetti, Giuseppe (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Primary research requests the recording of data through measurements, such as linear and angular parameters in cephalometric,strength of adhesion, skeletal maturation stages and so on. In all of these cases, an analysis of the method error, i.e. repeatability of the measurements, is a fundamental part of the study. In this paper, the case of the continuous data set will be taken into consideration.